Study on the Workability and Mechanical Properties of Low-Carbon Fair-Faced Concrete Incorporating Multiple Mineral Admixtures - Huang, Zhenyu; Yin, Jian (Scientific Journal of Technology, 2026)
To achieve coordinated optimization of workability and mechanical performance in fair-faced concrete, an ordinary Portland cement-based binder system incorporating fly ash (FA), ground granulated blast-furnace slag (BFS), metakaolin (MK), and diatomite (DE) was developed to prepare low-carbon fair-faced concrete with multiple mineral admixtures. An L16(44) orthogonal design was employed to systematically investigate the effects of these factors on spread diameter, T500, compressive strength at 3, 7, and 28 days, and splitting tensile strength at the same ages. Range analysis, analysis of variance, interaction analysis, and the entropy weight-TOPSIS method were further used for comprehensive evaluation. The results show that workability is mainly governed by FA and MK: FA improves flowability, whereas MK and DE increase system cohesiveness and impair fresh-state performance. The strength at all ages is dominated by BFS, indicating that slag powder is the key constituent for enhancing the mechanical properties of low-carbon fair-faced concrete. Comprehensive evaluation ranked the 16 mixtures in the order of L7, L8, and L4, with L7 exhibiting the best overall performance. The study demonstrates a clear need to balance workability and strength in systems containing multiple mineral admixtures, and that the synergistic use of moderate FA and relatively high BFS is more conducive to improving the overall performance of low-carbon fair-faced concrete.